Entre madres-adolescentes y adolescentes-madres: un análisis de su trayectoria de vida y los factores que influyen en su configuración - Mastro Naccarato, Irene Del (Pontificia Universidad Católica del Perú. Fondo Editorial, 2015)
The main objectives of this research, that took place in Lima between 2012 and 2013, were to analyze: a) the consequences of teenage motherhood in education, labor and family and b) the factors that influence the reconfiguration of the life trajectories of the teenage mothers after the pregnancy period. After interviewing thirteen teenage mothers that come from different socioeconomic backgrounds and whose children age range between 2-5 years old, we find two types of trajectories: a) the teenage mother trajectory and b) the teenage as mother trajectory. The results of this research suggest that the socioeconomic background, gender, teenage culture and motherhood, as well as the experiences, characteristics and aspirations of each woman are key factors that shape the life trajectories of teenage mothers.

Analizar las consecuencias de la maternidad adolescente en los ámbitos educativo, laboral y familiar, así como los factores que influyen en la reconfiguración de la trayectoria de vida de la madre adoles- cente tras el embarazo, son los principales objetivos de esta investigación realizada entre los años 2012 y 2013. A partir de trece entrevistas en profundidad a madres adolescentes con hijos entre 2 y 5 años de edad y provenientes de distintos estatus socioeconómicos de Lima, encontramos dos trayectorias tipo: la trayectoria madre adolescente y adolescente-madre. Los hallazgos de este estudio sugieren la importancia del estatus socioeconómico, los roles de género, las concepciones en torno a la adolescencia y al ejercicio de la maternidad, así como las vivencias, características y aspiraciones propias de cada mujer como factores que intervienen en la configuración de la trayectoria de vida de las madres adolescentes.
Between teenage mothers and teenagers as mothers: an analysis about their life trajectories and the factors that influence their configuration
Keywords: Adolescencia; Maternidad; Trayectorias; Sociology; Adolescence; Motherhood; Trajectories; https://purl.org/pe-repo/ocde/ford#5.04.00